Synergy of Legal Department and Regional Apparatus to Produce Quality Regent Regulations in Penajam Peser Utara Regency - Hastuti, Wulan Rudi; Hamid, Mulyadi; Hamzah, Nasir (Newinera Publisher, 2024)
This study examines the synergy between the Legal Division and regional apparatus in the process of formulating high-quality Regent Regulations in Penajam Paser Utara Regency. Using a descriptive qualitative approach through in-depth interviews, this research aims to explore the dynamics of interaction between these two key entities in policy-making, as well as the factors influencing the effectiveness of their synergy. The findings reveal that the synergy between the Legal Division and regional apparatus in Penajam Paser Utara Regency is generally well-established, although challenges still exist in terms of limited time for completion, complex bureaucratic processes, and limited human resources. Factors affecting this synergy include supportive leadership, understanding of procedures, and clear regulatory guidelines. This study recommends the enhancement of collaboration between the Legal Division and regional apparatus, structured task division, improvement of communication mechanisms, and the development of human resources to ensure the creation of higher-quality Regent Regulations.